Mikael Agricolan Uuden testamentin reunahuomautukset - Heininen, Simo (Suomi, 2023)
Michael Agricola's main work is the New Testament, published in 1548, a magnificent quarto volume of 700 pages with a hundred woodcuts. The basic text used was the Greek text published by Erasmus, Erasmus' Latin translation, the Vulgate, the Luther Bible and the Swedish Bible from 1541. The 450 marginal glosses come from the Luther Bible and the Swedish Bible. In his translation, Agricola distinguished "the Holy Spirit's own words," i.e. H. the Bible text, the prefaces and marginal glosses, which were only intended to provide "clearer understanding". The word of God is much more valuable than the word of man, so that the translator was closely tied to the text. A free translation was out of the question, let alone consciously improving the text. He was able to proceed more freely with the prefaces and marginal glosses. Most of the time he translated verbatim, but did not shy away from omissions, additions and changes when he deemed them appropriate. In this critical edition, Agricola's marginal glosses on the New Testament are printed in parallel with their sources.